Reagent controlled addition of chiral sulfur ylides to chiral aldehydes - Aggarwal, Varinder K.; Bi, Jie (Beilstein Journal of Organic Chemistry, 2005)
The degree of reagent and substrate control in the reaction of chiral sulfur ylides with chiral aldehydes has been investigated. Specifically, the reactions of the two enantiomers of the chiral benzyl sulfonium salt 1 with glyceraldehyde acetonide were studied in detail. Of the two new stereogenic centers created, it was found that the C1 stereochemistry was largely controlled by the reagent, whereas control at the C2 center was dependent on the aldehyde used. In one case, the trans isomer was produced via reversible formation of the intermediate betaine, whereas in the alternative case, the C2 center was under Felkin Anh/Cornforth control through non-reversible formation of the betaine. Thus, the aldehyde stereocenter influenced the degree of reversibility in betaine formation, which impacted on the stereocontrol at the C2 position.